Salmonella Effector SpvB Inhibits NF-κB Activity via KEAP1-Mediated Downregulation of IKKβ - Yang, Sidi; Deng, Qifeng; Sun, Lanqing; Zhu, Yuan; Dong, Kedi; Wu, Shuyan; Huang, Rui; Li, Yuanyuan (Frontiers in Cellular and Infection Microbiology, 2021)
Bacterial pathogens have a broad arsenal of genes that are tightly regulated and coordinated to facilitate adaptation to alter host inflammatory response and prolong intracellular bacterial survival. Salmonella enterica serovar Typhimurium utilizes a type III secretion system (T3SS) to deliver effector molecules into host cells and regulate signal transduction pathways such as NF-κB, thereby resulting in salmonellosis. SpvB, a pSLT-encoded cytotoxic protein secreted by Salmonella pathogenicity island-2 T3SS, is associated with enhanced Salmonella survival and intracellular replication. In this report, we characterized the effects of SpvB on NF-κB signaling pathway. We showed that SpvB has a potent and specific ability to prevent NF-κB activation by targeting IκB kinase β (IKKβ). Previous studies from our laboratory showed that SpvB decreases Nrf2 through its C-terminal domain. Here we further demonstrated that KEAP1, a cytoplasmic protein that interacts with Nrf2 and mediates its proteasomal degradation, is involved in SpvB-induced downregulation of IKKβ expression and phosphorylation. Reduction of KEAP1 by small-interfering RNA prevented the suppression of IKKβ and its phosphorylation mediated by SpvB. These findings revealed a novel mechanism by which Salmonella modulates NF-κB activity to ultimately facilitate intracellular bacterial survival and proliferation and delay host immune response to establish infection.